Wajah Sekolah Aman: “Eksplorasi Persepsi Siswa Kelas X Terhadap Risiko Kekerasan Seksual dan Perundungan” (Studi Kasus SMK Negeri 1 Selo) - Triananda Nur Khairin; Tri Mart Tianingsih; Talita Putri Lestari; Syafa Al Azhara Riberio; Luki Sri Anggorowati (Pusat Riset dan Inovasi Nasional, 2025)
Sexual violence and bullying are increasingly found in educational environments, including in Vocational High Schools (SMK). These issues have significant impacts on students’ mental health, safety, and academic performance. This study aims to identify the forms of sexual violence and bullying occurring in SMK, analyze the factors that contribute to these cases, and evaluate the prevention and intervention efforts implemented by the school. The research employs a quantitative method, distributing questionnaires to SMK students and conducting limited interviews with Guidance and Counseling teachers. The results show that verbal bullying, social bullying, and non-physical sexual harassment are the most common cases. The primary factors contributing to these incidents include weak school supervision and students’ limited literacy regarding behavioral boundaries related to sexual violence. Many students also refrain from reporting incidents due to fear, shame, or the perception that they will not receive support from their surroundings. These findings emphasize the necessity for schools to strengthen character education programs, improve teachers’ capacity for early detection and case handling, and enforce strict anti-violence policies. It is expected that this study can serve as a foundation for developing preventive strategies to create a safe, inclusive, and violence-free environment at SMK Negeri 1 Selo.